(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Lifestyle encompasses a set of activities aimed at maintaining and promoting health while preventing diseases. These include following a proper diet, balancing rest and activity, exercising regularly, controlling body weight, avoiding smoking and alcohol consumption, and enhancing immunity. Adolescence, a period marked by significant physiological and psychological changes, profoundly influences an individual’s lifestyle and health behaviours, shaping their health in adulthood.